Evaluation of Cardiac Functions and Rhythm in Pediatric Patients Diagnosed with Chronic Kidney Failure - Akkuş, Abdullah; Şap, Fatih; Ataş, Bülent; Oflaz, Mehmet Burhan; Baysal, Tamer (The European Research Journal, 2026)
Objectives: Chronic renal failure (CRF) represents a progressive and irreversible decline in renal function. Among individuals with end-stage renal disease (ESRD), cardiovascular disorders are recognized as the leading contributors to morbidity and mortality. The present study aimed to assess cardiac function in pediatric patients diagnosed with CRF. Methods: This cross-sectional study included 30 pediatric patients with CRF who were under follow-up between October 2018 and August 2019, along with 30 age- and sex-matched healthy controls. The CRF group was further divided into two subgroups according to dialysis status. For all participants, conventional 12-lead electrocardiography was performed, and indices associated with atrial (P-wave dispersion, Pd) and ventricular (QT dispersion, corrected QT dispersion, Tp–e, Tp–e/QT, Tp–e/QTc) arrhythmia risk were recorded. Each subject also underwent a detailed echocardiographic evaluation, including both conventional and tissue Doppler measurements. Results: Anthropometric characteristics and blood pressure values did not significantly differ between the patient and control groups. Apart from an increased mean corrected QT dispersion (QTcd), other electrocardiographic parameters were comparable between groups. Ejection fraction (EF) and fractional shortening (FS) values were lower in CRF patients compared with controls. LV mass index (LVMI) was significantly higher in the dialysis subgroup relative to the control group. Additionally, the myocardial performance index (Tei index) was markedly elevated in CRF patients (P<0.001). Conclusions: These findings underscore the need for comprehensive cardiac evaluation in children with CRF. Nonetheless, larger-scale studies are warranted to confirm and expand upon these observations.